PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE AMATCH DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM PADA SISWAKELAS VI SD NEGERI 1 TAMBEA KEC.POMALAA KAB. KOLAKA - Fatmawaty Fatmawaty (Jurnal Teknologi Pendidikan Madrasah, 2020)
The background of this research is that Islamic religious education teachers in carrying out the learning process in the classroom are still traditional by using the lecture method so that the learning outcomes are not optimal. The purpose of this study was to determine whether the application of the make a match cooperative learning model can improve learning outcomes in Islamic religious education subjects. this type of research is classroom action. The research subjects were students of class VI SDN 1 Tambea. Based on the research results, the results of teacher activity in cycle 1 were 70.8%, 79.1%, respectively 29.2%, 20.9% inactivity. Whereas in the second cycle respectively reached 87.5%, 91.6% inactivity reached 12.5%. The results of student activity in the first cycle were 66.6%, 75%, respectively, 33.4% inactivity. Meanwhile, student activity in silkus II was 87.5% inactivity and 12.5%. In the first cycle showed an increase in learning outcomes, while the increase in the presentation of student learning outcomes in cycle I was 66.66% with an average value of 74.04. However, the success indicator has not yet reached 75%, so it is continued in cycle II. In the second cycle student learning outcomes increased with presentation reaching 77.5% with an average value of 90.90.